The role of shocks and risks for the livelihoods of small scale fishing communities of Hadejia-Nguru Wetlands in Nigeria - Levison Chiwaula; Hermann Waibel (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2009)
This paper assesses the impact of risks and shocks on household welfare in the Hadejia-Nguru Wetlands in Nigeria. We use estimated income loss in consumption equations to assess the impact. Our findings identify death of an adult member, drought, and social conflict as important shocks in the area. These shocks are more significant in reducing household food consumption than non-food consumption. Additionally, we find that farming dependent households suffer more from social conflicts; fishing households suffer more from drought; while the impact of death of an adult member does not depend on household livelihood strategies. Since the shocks that significantly reduce household consumption are not specific to such communities, we conclude that fishing communities do not need special social protection policies but these should not be left out in these programs. Further research should consider understanding the roles of off farm activities as ex-ante risk mitigation strategies or ex-post coping strategies.
Keywords: 330